2022
DOI: 10.1063/5.0088538
|View full text |Cite
|
Sign up to set email alerts
|

Anion diffusion in two-dimensional halide perovskites

Abstract: Commercialization of halide perovskites in the semiconductor industry is hindered by their short-term stability. The instability of perovskites is closely interlinked with ionic diffusion. Historically, attempts to study diffusion in 2D perovskites mostly utilized electrical characterizations, but these characterizations pose a challenge in deconvoluting the impact of device architecture, interlayers, and ionic species. In this Perspective, we focus our attention on simple optical characterizations employed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…The (PEA) 2 PbBr 4 -(PEA) 4 NaBiI 8 heterostructure emission spectra provided in Figure b show the generation of a sharp new green emission feature originating from the inward migration of the iodine anions. The iodine anions migrate from the shell (PEA) 4 NaBiI 8 into the core (PEA) 2 PbBr 4 and give rise to a mixed-halide (PEA) 2 Pb­(Br x /I 1– x ) 4 . ,, With increasing temperature, the new feature continuously shifts from 515 nm toward 500 nm, indicating the increased extent of migration of the iodide from the Pb-free shell into the lead-based core, whereas the optical microscope images of the (2T) 2 PbI 4 -(2T) 4 AgBiBr 8 heterostructure show no change and the corresponding PL spectra also do not show any shift or generation of new features, as shown in Figure c,d, suggesting that the rigid polythiophene ligand can suppress anion migration similar to the observed behavior earlier reported Figure e,f shows the optical microscope images and PL spectra of the (PEA) 2 PbBr 4 -(PEA) 4 AgBiI 8 heterostructure, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The (PEA) 2 PbBr 4 -(PEA) 4 NaBiI 8 heterostructure emission spectra provided in Figure b show the generation of a sharp new green emission feature originating from the inward migration of the iodine anions. The iodine anions migrate from the shell (PEA) 4 NaBiI 8 into the core (PEA) 2 PbBr 4 and give rise to a mixed-halide (PEA) 2 Pb­(Br x /I 1– x ) 4 . ,, With increasing temperature, the new feature continuously shifts from 515 nm toward 500 nm, indicating the increased extent of migration of the iodide from the Pb-free shell into the lead-based core, whereas the optical microscope images of the (2T) 2 PbI 4 -(2T) 4 AgBiBr 8 heterostructure show no change and the corresponding PL spectra also do not show any shift or generation of new features, as shown in Figure c,d, suggesting that the rigid polythiophene ligand can suppress anion migration similar to the observed behavior earlier reported Figure e,f shows the optical microscope images and PL spectra of the (PEA) 2 PbBr 4 -(PEA) 4 AgBiI 8 heterostructure, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal lattice of metal-halide perovskites is considered soft and tolerant to defects, but this also facilitates ion diffusion predominantly through lattice distortion and structural defect sites . Consequently, hysteresis behavior and electrical poling effects are typically observed under device operation, reducing their operation lifetime and performance stability.…”
Section: Advantages Of Organic Semiconducting Cationsmentioning
confidence: 99%
“…Consequently, hysteresis behavior and electrical poling effects are typically observed under device operation, reducing their operation lifetime and performance stability. Among the ionic species in perovskite lattices, halides have the lowest diffusion energy barrier compared with metal cations and organic cations, either A site cations or bulkier LAs . In 2D perovskites with layered structures, ion diffusion happens both along the lateral direction (i.e., within the perovskite layer) , and vertically through the organic wells. , With the incorporation of bulkier organic semiconducting LAs with rigid backbone, it was observed that both vertical and lateral halide migration could be suppressed, which could lead to enhanced operational stability when bias is applied.…”
Section: Advantages Of Organic Semiconducting Cationsmentioning
confidence: 99%
“…[29][30][31] To the best of our knowledge, most of the studies on halide mixing or exchange have been reported with 3D perovskites whereas 2D metal halide perovskites have focused only on the film with an emphasis on excited state transport and stability. [32][33][34][35][36] In this study, we have investigated the cross-halide ion mixing using colloidal 2D lead halide perovskites by tracking in situ and ex situ spectroscopic changes. Concentration-and temperature-dependent exchange experiments allow for determining the kinetic rate constant and activation energy for halide ion mixing in 2D PEA and BA-based perovskites.…”
Section: Introductionmentioning
confidence: 99%